External cavity beam combining of 21 semiconductor lasers using SPGD - Montoya, Juan; Augst, Steven J; Creedon, Kevin; Kansky, Jan; Fan, Tso Yee; Sanchez-Rubio, Antonio (Applied optics. Optical technology and biomedical optics, 2012)
Active coherent beam combining of laser oscillators is an attractive way to achieve high output power in a diffraction limited beam. Here we describe an active beam combining system used to coherently combine 21 semiconductor laser elements with an 81% beam combining efficiency in an external cavity configuration compared with an upper limit of 90% efficiency in the particular configuration of the experiment. Our beam combining system utilizes a stochastic parallel gradient descent (SPGD) algorithm for active phase control. This work demonstrates that active beam combining is not subject to the scaling limits imposed on passive-phasing systems.